2015
DOI: 10.3391/mbi.2015.6.4.02
|View full text |Cite
|
Sign up to set email alerts
|

Twenty five years of invasion: management of the round goby Neogobius melanostomus in the Baltic Sea

Abstract: Biological invasions are increasing in frequency and the need to mitigate or control their effects is a major challenge to natural resource managers. Failure to control invasive species has been attributed to inadequate policies, resources or scientific knowledge. Often, natural resource managers with limited funds are tasked with the development of an invasive species control program without access to key decision-support information such as whether or not an invasive species will cause damage, and what the e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
28
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 35 publications
(30 citation statements)
references
References 70 publications
1
28
0
Order By: Relevance
“…For example, the invasion by the spiny water flea Bythotrephes longimanus (Leydig) into Lake Mendota (USA) caused a decline in water transparency that translated into a US$ 140 million loss (Walsh, Carpenter & Vander Zanden, 2016). A complete eradication of invasive species may prove very expensive or simply impossible (Doody et al, 2017;Ojaveer et al, 2015), but continued efforts to control invasive species may keep both densities and ecological footprints low. Harvest and consumption of invasive species represent one approach to achieve this goal that is consistent with the concept of renewal ecology (Bowman et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, the invasion by the spiny water flea Bythotrephes longimanus (Leydig) into Lake Mendota (USA) caused a decline in water transparency that translated into a US$ 140 million loss (Walsh, Carpenter & Vander Zanden, 2016). A complete eradication of invasive species may prove very expensive or simply impossible (Doody et al, 2017;Ojaveer et al, 2015), but continued efforts to control invasive species may keep both densities and ecological footprints low. Harvest and consumption of invasive species represent one approach to achieve this goal that is consistent with the concept of renewal ecology (Bowman et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Numerous studies have reported negative ecosystem effects in the wake of the invasion of round goby (Balshine, Verma, Chant & Theysmeyer, 2005;Demchenko & Tkachenko, 2017;Karlson, Almqvist, Skora & Appelberg, 2007;Kornis et al, 2012;Lauer, Allen & McComish, 2004;Oesterwind et al, 2017;Sapota, 2004;Schrandt et al, 2016), yet few attempts have been made to mitigate the effects (Dorenbosch et al, 2017;Ojaveer et al, 2015). One potential approach to reduce round goby numbers and the ecological footprint could be to develop a targeted fishery for the species.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, it has been suggested that these species can help reduce the population growth of the round gobies in the Baltic (Ojaveer et al 2015). It is plausible that the impaired escape response of infected round gobies to aerial attacks observed in this study might increase susceptibility to predation by the great heron and other birds that feed by striking from above.…”
Section: Discussionmentioning
confidence: 99%
“…In the Baltic Sea, it now dominates the catch in various coastal fisheries, and it is frequently found in offshore catches (Ojaveer et al 2015). Round gobies are like most fishes infected by numerous different parasites both in their native and invasive areas (Kvach et al 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Lawrence River region in much higher numbers than expected based on introduction effort (i.e., shipping frequency) and environmental conditions between these regions, it has been suggested that Ponto‐Caspian taxa are inherently better invaders than species from other regions (Casties et al., ; Leppäkoski et al., ; Ricciardi & MacIsaac, ). Some of those Ponto‐Caspian species, such as the zebra mussel Dreissena polymorpha , the amphipod Echinogammarus ischnus and the round goby Neogobius melanostomus , can have high impact on local communities and ecosystem functioning (Charlebois, Corkum, Jude, & Knight, ; Dermott, Witt, Um, & González, ; Ojaveer et al., ; Ricciardi, Neves, & Rasmussen, ). Changes in species communities and environments may open new niche opportunities for continuously introduced species and might be enhanced by predicted future climate change (Holopainen et al., ; IPCC, ).…”
Section: Introductionmentioning
confidence: 99%